Pembuatan Sensor Potensiometrik: ESI-PB(II) dengan Ionofor DBDA18C6 untuk Analisis Logam Pb dalam Sedimen Laut di Kawasan Teluk Palu - Ruslan Ruslan (Biocelebes, 2008)
A research have been done about “Season Effect on Heavy Metal Content Pb, Cu and Cd in cockle (Anadara granosa) on Tumbelaka Shore Palu by AAS Method. Distribution and concentration of metal Pb, Cu, and Cd on cockle muscle are not depend on weather or season of sample taking. Commonly, consentration of Pb and Cd in two season, wet season and dry season are undetected. Cu consentration in the wet season is 0,272 ppm in stasiun I while 0,295 ppm in station II. In the dry season, consentration of Cu is not detected. Key words: Season, Heavy Metal, Anadara granosa.